Erratum to: Effects of Pulse Shape and Polarity on Sensitivity to Cochlear Implant Stimulation: A Chronic Study in Guinea Pigs - Macherey, Olivier; Cazals, Yves (Advances in experimental medicine and biology, 2016)
In the original version of the chapter, the labels on the x-axis of Figure 2, panels A and B were wrong. This incorrect figure has been replaced with the below figure.In the original version of the chapter, the labels on the x-axis of Figure 2, panels A and B were wrong. This incorrect figure has been replaced with the below figure.